"In Every Decision I'm Making, I'm Thinking About My Son": How Children Motivate and Constrain the Labor Force Participation of Mothers With Disabilities. Issue 2 (June 2023) - Deming, Sarah M.
Although women's employment patterns are influenced by both the presence of children and the presence of a disability, these distinct statuses have largely been explored in isolation from each other. This research employed in-depth interviews with 32 current and former disability benefit recipients to explore the ways children shape the labor market decisions and behaviors of mothers with disabilities. Motherhood served as both a motivation for and a constraint to pursuing employment, with mothers operating under distinct cost–benefit frameworks shaped by their responsibility for children. The report concludes with recommendations for programs and policies that could most effectively facilitate labor market reengagement among a subpopulation of mothers who both want to and need to work but who face unique child-related constraints to employment opportunities.